Early manifestations of BPAN in a pediatric patient. Issue 12 (26th September 2014) - Okamoto, Nobuhiko; Ikeda, Tae; Hasegawa, Tatsuji; Yamamoto, Yuto; Kawato, Kazumi; Komoto, Tomohiro; Imoto, Issei
<x xml:space="preserve">Abstract</x> Neurodegeneration with brain iron accumulation (NBIA) comprises a clinically and genetically heterogeneous group of progressive brain disorders with several distinguishable subtypes. Recently, WDR45 mutations were reported in patients with β‐propeller protein‐associated neurodegeneration (BPAN), characterized by early intellectual disability followed by delayed progressive motor and cognitive deterioration with onset in the second to third decade. BPAN has a distinct brain magnetic resonance imaging (MRI) pattern showing iron deposition in the globus pallidus and substantia nigra. To date, many of the BPAN patients have been diagnosed in adulthood. Here, we report on 6‐year‐old girl with BPAN diagnosed by whole exome sequencing. She showed Rett syndrome‐like manifestations, a peculiar facial appearance and mildly elevated serum enzymes. Brain iron accumulation was detected by T2*‐weighted MRI and T2‐star weighted angiography (SWAN). This unique combination of clinical and neuroimaging features may be helpful for early diagnosis of BPAN. © 2014 Wiley Periodicals, Inc.